Farm power transition and access in Senegal: Patterns and constraints - Tadesse, Getaw; Goundan, Anatole; Sarr, Saer (African Association of Agricultural Economists, 2019)
This paper aims at documenting evidences on the patterns and constraints affecting the sequential and simultaneous transition of farm power use from manual to animal to engine. It also aims at exploring access to farm equipment through ownership and rental service. Based on a household data collected under the huge and ambitious project called ‘Senegal Agricultural Policy Project’, the result generally confirms the very low use of farm machinery powered by engines despite years of efforts to support agricultural mechanization programs. However, the use of improved farm equipment powered by animals has shown a sharp increase overtime. The study further demonstrated the variation of constraints in farm mechanization transitions defined by sources of power. While demand side constraints such as farm size and off-farm income are more important for machineries than animal plows, supply-side constraints such as rental overhead costs and membership to a producer’s organization are very critical for transition to engine power through facilitating rental service which is the dominant source of access to heavy machineries. Based on these findings, we discussed the strategic interventions that are needed to enhance and sustain agricultural mechanization uptakes in Senegal.